2011
DOI: 10.1016/j.jpainsymman.2010.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Fentanyl Buccal Tablets for Breakthrough Pain in Highly Tolerant Cancer Patients: Preliminary Data on the Proportionality Between Breakthrough Pain Dose and Background Dose

Abstract: Context. Cancer patients receiving high doses of opioids as background medication are challenging, and it would be useful clinically to know whether a rapid-onset opioid (ROO) for breakthrough cancer pain (BTcP) may be started at a dose proportional to the background opioid dose.Objectives. The aim of this study was to assess the efficacy and safety of the fentanyl buccal tablet (FBT) in doses proportional to the opioid dose administered for background analgesia in a sample of patients with BTcP who were recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 15 publications
(16 reference statements)
3
13
0
1
Order By: Relevance
“…These findings confirm preliminary observations in patients admitted to hospital units who were receiving high doses of opioids for background analgesia and who were effectively treated with proportional doses of FBT, without adding risks of occurrence of adverse effects [21]. As this approach could not be generalized due to the characteristics of the unit, this hypothesis was tested in another setting, like home care.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…These findings confirm preliminary observations in patients admitted to hospital units who were receiving high doses of opioids for background analgesia and who were effectively treated with proportional doses of FBT, without adding risks of occurrence of adverse effects [21]. As this approach could not be generalized due to the characteristics of the unit, this hypothesis was tested in another setting, like home care.…”
Section: Discussionsupporting
confidence: 79%
“…In addition, patients who had unstable background analgesia or more than four episodes of BTP/day were excluded. The criterion to define BTP was reported in previous studies [6,12,14,21]. From this sample, patients who were receiving opioids in doses of oral morphine equivalents equal or more than 60 mg daily were prescribed FBT in doses proportional to opioids used for background analgesia.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…24 No preference for 1 of the 2 products was given by patients who received both delivery systems. The other important finding is that both treatments in doses proportional to the basal opioid dose used for background pain were effective as well as tolerable, confirming experience accumulated through the years and the findings of some controlled studies, [13][14][15][16][17][18][19][20][21][22][23][24] even when higher doses were used. Finally, despite a similar analgesic trend, FPNS had a major impact at the intervals taken into consideration.…”
Section: Discussionsupporting
confidence: 62%
“…For instance, the only existing controlled study performed using a fentanyl buccal tablet has evidenced that proportional doses are more effective than the dose titration approach, without higher risks of adverse effects, 22 confirming a series of open-label studies in which proportional doses were highly effective and well tolerated. [13][14][15][16][17][18][19][20][21][22][23][24][25] Finally, there is clinical legend suggesting that the rescue dose of opioids for BTP should be 10% of the daily dose of scheduled opioids. Several studies of proportional doses have shown that to produce meaningful and clinical analgesic effects, it is necessary to administer 15 to 20% of the daily dose.…”
Section: Discussionmentioning
confidence: 99%